In Vitro Antimicrobial Activity Screening of Leucoagaricus leucothites and Determination of the Ethanol Extract Composition By Gas Chromatography/Mass Spectrometry - CANLI, Kerem; AKATA, İlgaz; YETGİN, Ali; BENEK, Atakan; ALTUNER, Ergin Murat (Duzce Universitesi Bilim ve Teknoloji Dergisi, 2020)
Macrofungi are good food resources, which have not only medicinal properties but are nutritive as well. For centuries they have been used for preventing several diseases including cancer, hypercholesterolemia and hypertension. They are also known to present antimicrobial activity, thus the aim of the present study is to put forward antimicrobial activity of ethanol extract of Leucoagaricus leucothites (Vittad.) Wasser 1977, a macro fungi and in addition to determine the chemical composition by Gas Chromatography-Mass Spectrometry. Nineteen bacteria strains and one yeast strain are used in antimicrobial screening. According to the data obtained from the study L. leucothites presented both antibacterial and antifungal activity against the bacteria and yeast strains used at different concentrations with different levels. Although there are some previous studies, it can be proposed that this study is the first detailed screening report regarding the antibacterial and antifungal potential of L. leucothites and the compounds found in L. leucothites ethanol extract.
Keywords: Leucoagaricus leucothites; Mushroom; Antimicrobial activity; Chemical composition; Disk diffusion method; GC-MS; GC-MS; Technology; Science (General); Science; Mühendislik; gc-ms; disk difüzyon yöntemi; disk diffusion method; kimyasal bileşim; Q1-390; Engineering; mushroom; chemical composition; antimikrobiyal aktivite; antimicrobial activity; T; Q; Leucoagaricus leucothites; Mantar; Antimikrobiyal aktivite; Kimyasal bileşim; Disk difüzyon yöntemi; GC-MS; GC-MS; Engineering (General). Civil engineering (General); mantar; TA1-2040; leucoagaricus leucothites; 3. Good health